(untitled) (Revista Puertorriqueña de Psicologia, 2016)
The purpose of this study was to compare the level of life satisfaction of three groups: young employees, aged employees, and retired persons. The life Satisfaction Scale of Neugarten, Havighurst & Toin (1961) was administered to a sample of 313 research participants. The statistical analyses detected statistical differences between the means scores of participants 40 years old and less and participants 50 years old and more, the first group obtaining a higher mean score. Also, statistical differences were found between male aged employees and female aged employees, obtaining the male group a higher mean score.